2014
DOI: 10.1016/j.epsl.2014.08.033
|View full text |Cite|
|
Sign up to set email alerts
|

Optimizing multi-station earthquake template matching through re-examination of the Youngstown, Ohio, sequence

Abstract: A series of earthquakes in 2011 near Youngstown, OH, has been a focal point for discussions of seismicity induced by a nearby wastewater disposal well. Utilizing an efficient waveform template matching procedure, the optimal correlation template to study the Youngstown sequence was identified by varying parameters such as the stations utilized, frequency passband, and seismogram length. A catalog composed of 566 events was identified between January 2011 and February 2014. Double-difference relocation refines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 20 publications
0
80
0
Order By: Relevance
“…One possible difference between tectonic and induced events is the occurrence of smaller magnitude foreshocks which may migrate systematically away from the injection site [e.g., Bachmann et al , ; Skoumal et al , ]. Migration patterns that largely meet these criteria were observed close to injection site K r where several smaller magnitude earthquakes preceded a M L 3 ( K r 87) and a M L 4.6 ( K r 85) main shocks (inset Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…One possible difference between tectonic and induced events is the occurrence of smaller magnitude foreshocks which may migrate systematically away from the injection site [e.g., Bachmann et al , ; Skoumal et al , ]. Migration patterns that largely meet these criteria were observed close to injection site K r where several smaller magnitude earthquakes preceded a M L 3 ( K r 87) and a M L 4.6 ( K r 85) main shocks (inset Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Sensitive seismic monitoring and efficient earthquake detection algorithms using waveform similarity can be useful to refine earthquake catalogs in different parts of the central and eastern United States ( 22 ). This will help in applying the SI model in regions where the number of earthquakes above the completeness magnitude is currently not large enough to reliably calibrate the SI model.…”
Section: Discussionmentioning
confidence: 99%
“…to or larger than those for tectonic earthquakes [Shapiro et al, 2011;Bachmann et al, 2012]; however, studies on induced earthquakes in hydrocarbon reservoirs have found lower values [Friberg et al, 2014;Skoumal et al, 2014Skoumal et al, , 2015. Rabak et al [2010] observe a b value of 0.9 for the 2011 Enola swarm (~20 km southeast of the Guy-Greenbrier region) and speculate that natural fluid migration may trigger the swarm.…”
Section: 1002/2015gl065170mentioning
confidence: 99%
“…As implemented previously to detect low-frequency earthquakes [e.g., Shelly et al, 2007], earthquake swarms [Barrett and Beroza, 2014], and induced earthquakes [Skoumal et al, 2014[Skoumal et al, , 2015, the technique is based on the waveform similarity between known template events and detected earthquakes. We use the waveforms of the catalog events as template events, including both P and S waves, band-pass filtered between 1 and 20 Hz, and search for waveform matches with cross-correlation coefficients larger than a detection threshold (Figure 1b).…”
Section: Detection Of Additional Events Using Single-station Templatementioning
confidence: 99%